L-plastin regulates the stability of the immune synapse of naive and effector T-cells - Wabnitz, Guido H.; Balta, Emre; Samstag, Yvonne (Advances in Biological Regulation, 2017)
T-cells need to be tightly regulated during their activation and effector phase to assure an appropriate defence against cancer or pathogens and - vice versa - to avoid autoimmune reactions. Regulatory signals are provided via the immune synapse between T-cells and antigen-presenting cells (APCs) or target cells. The stability and kinetics of immune synapse formation is critical for proper T-cell functions. It requires dynamic rearrangements of the actin cytoskeleton necessary for organized spatio-temporal redistribution of receptors and adhesion molecules. We identified glucocorticoid-sensitive phosphorylation of serine 5 on the actin-bundling protein L-plastin as one important signalling event for this regulation. Using imaging flow cytometry as well as confocal and super-resolution microscopy we showed that L-plastin relocalizes to the immune synapse upon antigen encounter, where it associates with the β2-subunit of LFA-1 (CD11a/CD18). Interfering with L-plastin expression or activation leads to a defective LFA-1 recruitment and unstable T-cell/APC contacts. Consequently, the lack of L-plastin diminishes T-cell activation, proliferation and proximal effector responses such as cytokine production. On the other hand, a pro-oxidative milieu leads to prolonged activation of L-plastin resulting in a stronger enrichment of LFA-1 in the cytolytic immune synapse. Concomitant stabilization of conjugates formed by cytotoxic T-cells (CTLs) and their target cells impairs the ability of CTLs to kill more than one target cells (serial killing), which de facto leads to a downregulation of T-cell cytotoxicity. Together, we demonstrate that activation and spacial distribution of L-plastin regulates the maturation and stability of activating and cytolytic immune synapses important for T-cell activation and effector functions.